Effects of Lantana camara Invasion on Riparian Vegetation in Uttarakhand: A Case Study from the Garhwal Himalayas - Parveen Kumar Dobhal; Ravinder Kumar Kohli; Daizy Rani Batish (African Journal of Environmental Economics and Management, 2024)
Lantana camara L. (Verbenaceae), an exotic from tropical America, has invaded vast areas of forests surrounding Nayar River in Garhwal Himalayas (Uttarakhand, India). Several factors like high reproductive potential, absence of preferred predators, evergreen nature and sufficient moisture provided by river water favour extraordinary growth of L. camara in this area. In this study, the impact of L. camara invasion on basal area cover, density, frequency and abundance of various plant species was determined. Invasion was able to change the quality (composition, distribution) and quantity (growth in number and size) of different species in this region. The invasion was also found to have some relation with native-exotic nature and different plant habits (like tree and herbs) of local flora. As determined by various ecological indices, there was significant loss of species richness and diversity in invaded localities. In total, there was a 28.4% decrease in species richness of invaded localities. Excluding L. camara, nearly 63% loss of basal area of vegetation was recorded in the invaded localities compared to not invaded ones. There was also an impression that L. camara favoured exotics over endemic species in this riparian zone.